Drei textkritische Probleme in der ersten Ekloge des Calpurnius - Ullrich, Heiko (Wiener Studien, 2023)
In this paper I will discuss three passages in Calpurnius Siculus' first Eclogue whose text is disputed: In Calp. ecl. 1,35 Jan van Vliet's conjecture fatis has nearly erased the transmitted fagis from both editors' and interpreters' memory, in 1,57 a simple scribe's error has led to otherwise unsubstantiable guesses about a substantive *discordium, and in 1,76 the splitted transmission which has both fervit and servit can be decided in favour of the latter by a closer look at the context.